Fraksinasi Ekstrak Metanol Buah Parijoto (Medinilla speciosa Blume) dengan Pelarut Metanol, Etil Asetat, dan N-Heksana - Nailil Mona; Dyah Ayu Widyastuti; Atip Nurwahyunani; Fafa Nurdyansyah (UNIVERSITAS PGRI MADIUN, 2022)
Parijoto fruit (Medinilla speciosa Blume) is an endemic fruit around Mount Muria, Kudus, Central Java. The native people utilize Parijoto as traditional herbal medicine. Those utilization due to its metabolite compounds, such as tannin, flavonoid, fenolic, terpenoid, etc. In order to utilize Parijoto fruit properly, it is necessary to have an appropriate extraction and fractination method. So, the bioactive compounds of Parijoto fruit can be optimally extracted. The objective of this study is to obtain fractions of Parijoto fruit using three different solvent, methanol, ethyl acetate, and n-hexane. This study perform maceration as extraction method and liquid-liquid fractination to obtain the fractions. The dry simplicia yield was 85.49%. The maceration result was in the form of a blackish red green liquid with 67.45% yield. The methanol fraction was a thick blackish red liquid with 45.4% yield. While, the ethyl acetate fraction was a slightly fibrous viscous liquid with pinkish milk brown colour and 22.8% yield. On the other hand, the n-hexane fraction was a greenish viscous liquid with 13.8% yield. The highest yield is the result of fractination with methanol as a solvent because it is the most polar among others in this study. The solvent polarity is greatly affects the yield of fractination from natural product materials. In this study, the order of Parijoto yield from the highest to the lowest is methanol fraction, ethyl acetate fraction, and the last is n-hexane fraction. Those results were obtained due to the differences of each solvent polarity.